Hubungan Cash Holding dan Nilai Perusahaan di Indonesia - Sutrisno, Bambang (Jurnal Dinamika Akuntansi dan Bisnis, 2017)
This paper aims to examine the effect of cash holding on firm value in Indonesia. This study tested empirically for the existence of a linear relationship between cash holding and firm value. Then the study examines whether or not a quadratic relationship exists. A total of 115 manufacturing firms listed on the Indonesia Stock Exchange from 2010 to 2014 were examined. This study employs panel regression with fixed effect model. The results show that a linear relationship exists between cash holding and firm value. However, a quadratic relationship does not appear between cash holding and firm value of Indonesian manufacturing firms. Thus, the result of this study supports pecking order theory